ﺗﻌﻠﻴﻢ اﻟﻤﻔﺮدات اﻟﻌﺮﺑﻴﺔ ﺑﺎﺳﺘﺨﺪام اﻟﻐﻨﺎء ﻟﺘﺮﻗﻴﺔ ﻣﻬﺎرة ﻛﻼم - Ahmala, Majidatun; Syarifah, Ainun; Fitria, Ria; Taqiyah, Siti Zaimatut; Tiasaji, Diana Putri (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Vocabulary is one of the important elements in language because it contains the meaning and use of words in the language of the speakers themselves or from the author. And the person will improve his language skills if he increases his vocabulary because the competence of the person’s language skills is in accordance with the vocabulary he absorbs. In teaching vocabulary, educational aids are needed to help students in understanding, and linguistic tools are an important requirement that teachers must use to facilitate foreign language teaching. teach vocabulary related to the subject, including song, and this stems from the new strategy. The problem of this research is "How to teach Arabic vocabulary by using singing to improve speaking skills". The research method used in this study is a qualitative research method. And the method of collecting data is by studying the literature through books and several journals. The result of this research is that singing can be used to improve speaking skills to increase vocabulary by making all the vocabulary in singing textbooks popular.